EDUKASI DAN PELATIHAN PEMBUATAN TEH HERBAL DARI BUNGA KECOMBRANG SEBAGAI UPAYA PENCEGAHAN DAN PENGENDALIAN DIABETES MELLITUS - Gultom, Evi Deviana (Jurnal Pengabdian Masyarakat Putri Hijau, 2025)
Diabetes mellitus is a serious health problem in Indonesia, which ranks fifth in the world for the highest number of diabetics. The high prevalence, along with the side effects and cost of pharmacological treatments, encourages the need for supportive alternatives. This community service aims to increase the understanding and awareness of the Mekar Sari Village community regarding the prevention and management of diabetes mellitus through the utilization of torch ginger flower (Etlingera elatior) as an herbal tea. Torch ginger flower contains bioactive compounds such as flavonoids and polyphenols that have anti-hyperglycemic potential by inhibiting α-glucosidase and α-amylase enzymes. This activity will be held on Friday, September 26, 2025, at the Mekar Sari Village Office in Deli Tua. The methods used include health education, training on how to make the herbal tea, a question-and-answer session, and health screening. Through this activity, it is expected that the community can independently utilize torch ginger flower as a supportive therapy that is easy to process, affordable, and holistic to control diabetes mellitus and improve their quality of health.